Do Reconhecimento de Estado e de Governo no Direito Internacional (Meridiano 47 - Journal of Global Studies, 2017)
This article approaches the subject related to the recognition of states and governments in International Law from a jurisprudential and state practice perspective. It is presented three stages of evolution of this issue in order to describe its main characteristics, and to trace the outline of jurisprudence and state practice related to the recognition of states and government in the post-cold war context.